Lipomatous Hypertrophy of the Atrial Septum in a Patient Undergoing Coronary Artery Bypass Surgery - Thomas Strecker; Michael Weyand; Abbas Agaimy (Case Reports in Pathology)
Background. Lipomatous hypertrophy of the atrial septum (LHAS) is a rare entity characterized by mass-forming deposition of fatty tissue within the atrial septum. To date, <300 cases have been reported; many of them were autopsy findings. The clinical presentation of LHAS varies from incidental asymptomatic mass (most frequent form) to severe life-threatening cardiovascular complications necessitating emergency cardiac surgery. Case Presentation. Here, we present the successful surgical resection of such a massive LHAS which was found incidentally on preoperative investigation of a 71-year-old patient with progressive coronary heart disease. Histology confirmed the diagnosis of lipomatous hypertrophy of the atrial septum. Conclusions. The described case report illustrates an unusual example of LHAS in a patient undergoing a planned coronary artery bypass surgery. In this case, surgical intervention was justified to avoid later outflow obstructions.